2010
DOI: 10.1021/la1040954
|View full text |Cite
|
Sign up to set email alerts
|

Pressure/Electric-Field-Assisted Micro/Nanocasting Method for Replicating a Lotus Leaf

Abstract: An electric field-aided process was introduced for a curable casting process. As a micro/nanosized pattern mask, a lotus leaf, which has a hierarchical structure, was used. The process consists of two steps: (1) applying an electric field to a liquid polymer and solidifying the polymer for use as a negative mold, and (2) using the negative polymer mold to fabricate a replicated poly(ethylene oxide) (PEO) surface in the original shape of the lotus leaf. In this process, the applied electric field induces unstab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…During this process, the electric field vibrates the liquid PDMS, causing unstable flow motion to the surface of the hierarchical pattern on the plant leaf. With increasing electric field strength, high flow movement is achieved and eventually enhances the efficiency of the pattern transfer . This technology is similar to the principle of the electrowetting process, which has been defined as a change in solid‐electrolyte contact caused by an applied electric potential difference between them .…”
Section: Fabrication Methods For Obtaining Patterned Surfacesmentioning
confidence: 97%
See 1 more Smart Citation
“…During this process, the electric field vibrates the liquid PDMS, causing unstable flow motion to the surface of the hierarchical pattern on the plant leaf. With increasing electric field strength, high flow movement is achieved and eventually enhances the efficiency of the pattern transfer . This technology is similar to the principle of the electrowetting process, which has been defined as a change in solid‐electrolyte contact caused by an applied electric potential difference between them .…”
Section: Fabrication Methods For Obtaining Patterned Surfacesmentioning
confidence: 97%
“…Schematic representation of the plasma lithography process for template‐guided self‐assembly. (d) Electric field‐aided micro/nanocasting . A schematic of alternating current field aided micro/nano‐casting technique with parallel electrodes.…”
Section: Fabrication Methods For Obtaining Patterned Surfacesmentioning
confidence: 99%
“…It is still a challenge to copy natural superhydrophobic surfaces with features of 5 nm or less, although application of high electric fields has been found to improve copy fidelity in both the negative and the positive copy. 53 Other possibilities include increased pressure and the application of ultrasound. 54 Other polymers have also been cast against harder, more heat resistant substrates and have shown some success.…”
Section: Casting and Moldingmentioning
confidence: 99%
“…The surface of the SBS-DFHMA coatings were also observed (Figure 5c,d) and the images were used for comparison. The images shown that SBS-DFHMA coating surface was smooth, but hybrid coating surface existed many projections in microns size with secondary projections in hundred nanometers which was similar to microstructure of the lotus leaf surface with super-hydrophobic [12]. There were two reasons for the forming of nano-projections with the additions of the micron-particles in the hybrid coatings: the surface roughness caused by the exist of the pore structure and differences in nano size of the b c particles which accumulated together.…”
Section: Mesoporous Silica(sba-15)mentioning
confidence: 81%